2005
DOI: 10.1021/nl051921g
|View full text |Cite
|
Sign up to set email alerts
|

Raman Microprobe Analysis of Elastic Strain and Fracture in Electrophoretically Deposited CdSe Nanocrystal Films

Abstract: The mechanical stability of nanocrystal films is critical for applications, yet largely unexplored. Raman microprobe analysis used here to probe the nanocrystal cores of thick, fractured electrophoretically deposited films of 3.2 nm diameter CdSe nanocrystals measures approximately 2.5% in-plane tensile strain in cores of unfractured films. The crack dimensions determine the overall in-plane film strain, approximately 11.7%, and the film biaxial modulus, approximately 13.8 GPa, from which the biaxial modulus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 16 publications
6
50
0
Order By: Relevance
“…The value of the elastic modulus previously deduced indirectly via Raman spectroscopy of the CdSe cores under tension for the 3200 nm EPD film described in Table I (9.7 GPa, assuming 0:3) [13] is very similar to that measured here via nanoindentation ( 8 GPa) in which the deformation is largely compressive.…”
supporting
confidence: 77%
“…The value of the elastic modulus previously deduced indirectly via Raman spectroscopy of the CdSe cores under tension for the 3200 nm EPD film described in Table I (9.7 GPa, assuming 0:3) [13] is very similar to that measured here via nanoindentation ( 8 GPa) in which the deformation is largely compressive.…”
supporting
confidence: 77%
“…As shown in Fig. 7, the peak at 460 cm -1 is the characteristic band for CdSe QDs (25). Comparing with the previous reported results, the shift of the Raman peaks may be due to the changes of the QDs sizes.…”
Section: The Mechanism Of Reaction Between Thiols and Cdse Qdssupporting
confidence: 63%
“…In dried films of quantum dots, Raman spectroscopy has shown that the dots may be strained. 24 However, if strain 12 or electric field 11 were the source of the large shifts or long tail, all three systems should behave similarly, therefore the absence of such effects for CdSe/ZnS suggests that these effects are weak.…”
Section: Discussionmentioning
confidence: 99%